Issues faced by hotel human resource managers in Alexandria, Egypt - Eslam Ahmed Fathy Fathy (Research in Hospitality Management, 2018)
This study investigates challenges faced by human resource (HR) managers and their practices to cope in hotels of Alexandria city, Egypt. The researcher undertook semi-structured interviews with HR managers in four- and five-star hotels in Alexandria. The study findings revealed several themes related to HR challenges faced by HR managers in the process of recruitment, selection, training, turnover and retention. Fortunately, customs and traditions have become limited in adversely affecting work in hospitality, except for married women. The coping practices adopted by HR managers are discussed. The study implications are put forward to HR managers to overcome the HR challenges in the hotel industry, such as conducting a cooperation protocol between hotels and academic institutions, developing educational hotels with faculties, institutions and hotel schools, or signing cooperation protocols with neighbouring hotels. By improving employment conditions and rewards, the negative trends can be reversed. Finally, the paper acknowledges research limitations and makes suggestions for future research, such as other hospitality sectors, hotel grades, geographical areas, and the whole of Egypt.